2018
DOI: 10.1097/hjh.0000000000001769
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-19a/b-3p protect the heart from hypertension-induced pathological cardiac hypertrophy through PDE5A

Abstract: Aim:PDE5A is a leading factor contributing to cGMP signaling and cardiac hypertrophy. However, microRNA-mediated posttranscriptional regulation of PDE5A has not been reported. The aim of this study is to screen the microRNAs that are able to regulate PDE5A and explore the function of the microRNAs in cardiac hypertrophy and remodeling.Methods and Results:Although miR-19a/b-3p (microRNA-19a-3p and microRNA-19b-3p) have been reported to be differentially expressed during cardiac hypertrophy, the direct targets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…A striking demonstration supported that miR-19a/ b family could promote proliferation and survival of ischemic neural progenitor cells and primary cardiomyocytes, and revealed the potential capability of miR-19a/b in cardiac repair and regeneration [32]. Besides, miR-19a-3p was also evaluated to inhibit cardiac hypertrophy, cardiac remodeling and heart failure [33]. Importantly, Gao et al have stated that overexpression of miR-19a/19b substantially diminished Cleaved caspase3 levels and inflammation, preserved cardiac function and reduced infarct size, thus showing therapeutic roles in cardiac regeneration and protection from myocardial infarction [20].…”
Section: Discussionmentioning
confidence: 76%
“…A striking demonstration supported that miR-19a/ b family could promote proliferation and survival of ischemic neural progenitor cells and primary cardiomyocytes, and revealed the potential capability of miR-19a/b in cardiac repair and regeneration [32]. Besides, miR-19a-3p was also evaluated to inhibit cardiac hypertrophy, cardiac remodeling and heart failure [33]. Importantly, Gao et al have stated that overexpression of miR-19a/19b substantially diminished Cleaved caspase3 levels and inflammation, preserved cardiac function and reduced infarct size, thus showing therapeutic roles in cardiac regeneration and protection from myocardial infarction [20].…”
Section: Discussionmentioning
confidence: 76%
“…HDAC3 is a major histone deacetylase, and its enzyme activity is the target of small molecule inhibitors in the treatment of various diseases 21 . Studies have shown that HDAC3 expression is downregulated in ischemic myocardial injury 22 and hypertrophic cardiomyocytes 12,23 . CDK2 also plays an important role in the regulation of apoptosis in MIRI 15 .…”
Section: Resultsmentioning
confidence: 99%
“…21 Studies have shown that HDAC3 expression is downregulated in ischemic myocardial injury 22 and hypertrophic cardiomyocytes. 12,23 CDK2 also plays an important role in the regulation of apoptosis in MIRI. 15 In order to further study the effects of mir-19a-3p, HDAC3, and CDK2 on MIRI, we detected their expression in rat myocardial tissues using RT-qPCR and Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple mechanisms for the progression of hypertension to HTN-LVH, heart failure or cerebral hemorrhage. For instance, miR-19a/b-3p defenses the heart from pathological myocardial hypertrophy induced by hypertension via targeting PDE5A [15]. Up-regulated miR-133 can attenuate agonist-induced cell hypertrophy [16], balk myocardial brosis [17], and modulate heart development and normal heart function.…”
Section: Discussionmentioning
confidence: 99%